Color Judgments of #The Dress and #The Jacket in a Sample of Different Cultures. (March 2021) - Kawasaki, Yayoi; Reid, J. Nick; Ikeda, Kazuhiro; Liu, Meiling; Karlsson, Bodil S. A.
Two viral photographs, #The Dress and #The Jacket, have received recent attention in research on perception as the colors in these photos are ambiguous. In the current study, we examined perception of these photographs across three different cultural samples: Sweden (Western culture), China (Eastern culture), and India (between Western and Eastern cultures). Participants also answered questions about gender, age, morningness, and previous experience of the photographs. Analyses revealed that only age was a significant predictor for the perception of The Dress, as older people were more likely to perceive the colors as blue and black than white and gold. In contrast, multiple factors predicted perception of The Jacket, including age, previous experience, and country. Consistent with some previous research, this suggests that the perception of The Jacket is a different phenomenon from perception of The Dress and is influenced by additional factors, most notably culture.